TELAAH KRITIS SYARAT MUFASSIR ABAD KE-20 - Imam Masrur (QOF, 2018)
There is reluctance by some scholars today to reinterpret the Qur'an, because it is guided by a number of strict conditions proposed by classical scholars. On the other hand, in this millennial era we can find a number of people who interpret the Qur'an, even though they do not have a qualified scientific capacity. This makes the Koran the first to be a clue, but instead applies the opposite due to the carelessness of the interpreter. Responding to this phenomenon, it is important to study further about what conditions must be met by the interpreter in this millennium, both from the mental aspect (personality) and from scientific capacity. This research was conducted using comparative methods and data analysis with theory Socrates dialectic. A number of findings from this study included: first, differences in the determination of the conditions that must be fulfilled by the mufassir, among ulama actually constitute a form of ijtihad and the prudence of previous scholars, and are not an absolute requirement that cannot be contested, and can change according to the conditions. Secondly, there are six mental conditions that have to be universally interpreted, namely: true aqeedah, clean from lust, good intentions and true goals, obedience and practice of knowledge, holding fast to the sunnah, exerting energy to learn or equipping yourself with science, while the memorization of the Qur'an is a temporal and flexible requirement. Third, the scientific qualifications of the universal interpreter should master a number of the following scientific disciplines, namely: the science of Arabic, ulum al-Qur'an, ulum al-hadis. In addition, supporting knowledge is needed such as medical science related to verses concerning the medical field, astronomy related to astrology verses, and other sciences, all of which are local, temporal and flexible.